Sexual dimorphism in Autogneta, with description of three new species from North America and new diagnosis of the genus (Acari, Oribatida, Autognetidae) - Behan-Pelletier, Valerie M. (Zootaxa, 2015)
Species in the oribatid mite genus Autogneta are primarily Palaearctic, with a few, mainly unidentified records from North America. Strong sexual dimorphism is reported in the genus for the first time; it is expressed by a posterior porose region on the male notogaster that in some species is associated with modifications of notogastral setae h1 and p1. Herein, I describe 3 new dimorphic Autogneta species from North America, based on adult specimens: A. aokii sp. nov. and A. schusteri sp. nov., from California, USA, and A. flaheyi sp. nov., from British Columbia and Alberta, Canada. New diagnoses for 2 other dimorphic species, the type species Autogneta longilamellata (Michael) and A. amnica Jacot, are presented that accommodate their previously unreported dimorphic males. Autogneta flumengalei Jacot is recombined as Conchogneta flumengalei (Jacot) comb. nov. Finally, I give a key to adults of Autogneta species known from North America.